ANALISIS MONITORING DASHBOARD GANGGUAN LOGIC PADA INDIHOME - Dedeh Widia Ningsih; Ibrahim Lammada; Arnisa Stefanie (Politeknik Harapan Bersama Tegal, 2021)
Abstract - Analysis of the logic disturbance dashboard monitoring on the WITEL Karawang indihome. Monitoring at indihome is a necessity to support the performance of Telkom Indonesia employees, monitoring is very necessary so that it can monitor using the Ibooster and Embassy applications which are monitored directly by several operators so that it will make monitoring easier and more practical, then the results of this monitoring will be reported directly to indihome technicians. . Through this kind of monitoring, technicians can work more easily to find damage caused by physical or logical problems. After the technician gets a direct report from the operator and if the damage is caused by physical disturbance, the technician will immediately repair the location of the damage, this monitoring dashboard will continuously provide reports from the conditions in place.In this way, the technician can solve problems that arise without waiting for reports from users. and wireless based Internet technician at WITEL Karawang. Easy to maintain stability based on wireless Internet without directly checking equipment.